1994
DOI: 10.1017/s0030605300028672
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary survey of Kounounkan Forest, Guinea, West Africa

Abstract: Biological studies in Guinea have been very patchy, leaving much of the country almost unsurveyed. In 1992 the Fauna and Flora Preservation Society funded a 10-day field visit to Kounounkan, a relict forest at the northern edge of the Upper Guinea Forest Block. The survey found a variety of habitats and high biodiversity, including two vulnerable and one endangered species. Hunting pressure appears to be low and the site is very well suited for the development of further conservation initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Gippoliti & Dell'Omo (1995) also reported observing chimpanzee nests in E. guineensis trees in Guinea-Bissau. Moreover, Barnett et al (1994) and observed a similar phenomenon on Mount Nimba in Guinea. Kortlandt (1996) reported observing chimpanzee nests in this species since 1965 in Guinea.…”
Section: Discussionsupporting
confidence: 52%
“…Gippoliti & Dell'Omo (1995) also reported observing chimpanzee nests in E. guineensis trees in Guinea-Bissau. Moreover, Barnett et al (1994) and observed a similar phenomenon on Mount Nimba in Guinea. Kortlandt (1996) reported observing chimpanzee nests in this species since 1965 in Guinea.…”
Section: Discussionsupporting
confidence: 52%
“…Finally, a vision of what a complete protected area network entails, can greatly aid a country in determining its management needs and thus conservation planning in the long term. Barnett et al (1994Barnett et al ( , 1996 a Taxonomy follows Duff and Lawson (2004); b See text (''Method'' section) and Table 5 (2005) Pelosi (2000) Pelosi (2000) Brugière et al (2005,2006), Wright et al (2007a) Ham (1998) Biodivers Conserv (2009) 18:847-868 863 …”
Section: Resultsmentioning
confidence: 99%
“…The Kounounkan Massif is situated in Forécariah Prefecture in western Guinea and is the south-eastern section of an expanse of sandstone plateaus occupying much of Coyah, Kindia and Dubreka Prefectures. The Kounounkan Massif is an area of mixed primary and secondary closed forest with natural and man-made savannah and farmbush (Barnett & al. 1994).…”
Section: Introductionmentioning
confidence: 99%